Homelessness in the light of constitutional law enforcement (Academic Journal of Internal Affairs, 2019)
As a result of a legislation process since 2010 reached Hungarian legislation the actual situation that homelessness became a criminal act on every public area. The work is looking for answers for two questions. One of them is how can criminalisation of homelessness match to constitutionality, resp. to principles and values of European lifestyle. The other question aims to show the limits of constitutional law enforcement, i.e. can law enforcement be authorised to interferences for solution of a social problem even without a hazardous situation. The author clears and presents the legislation process leading to criminalisation interpreting that in the special view of law enforcement. Here are presented term problems resulting in uncertainties for law application that are difficult to manage by law enforcement of constitutional democracies. As a result of them all will be outlined the limits of constitutional law enforcement making it unable to handle social life situations.
Keywords: homelessness; policing; constitutional assessment